Sustainable Healthy Working Life for All Ages-Work Environment, Age Management and Employability - Nilsson, Kerstin; Midtsundstad, Tove; Lundqvist, Peter; Crawford, Joanne; Nygård, Clas-Håkan (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The reprint "Sustainable Healthy Working Life for All Ages-Work Environment, Age Management and Employability" provide an outlet of research contributing to the development of theoretical and practical knowledge influencing people's working life. Working life is complex and there are many different factors that influence, such as the demographic change, pandemic and rapid technological development, etc., which place constantly changing demands on both employees, organizations/companies and society in different countries. This reprint covers new knowledge, as identified factors and areas that affect employees' ability to work to an older age, interventions and measures that enable a healthy and sustainable working life throughout the entire working life journey, from young to senior employees. The reprint also addresses the pressured work situation of school leaders in managing the education of children and young people in society, and what makes them stay or leave their jobs. In addition, the reprint addresses the way in which the Covid-19 pandemic has affected working life, not least for the health care professional groups and organizations.